2018
DOI: 10.1177/1049909118763796
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivational Interviewing to Engage Latinos in Advance Care Planning: A Community-Based Social Work Intervention

Abstract: This study contributes to the literature by identifying areas for adaption to enhance understanding and increase information to ultimately achieve the completion of ACP among Latinos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…[7][8][9][10][11] Known barriers to ACP include individual (eg, knowledge, attitudes) and health system level (eg, complexity of advance directive forms, lack of clinician training) factors. However, despite development of patient-and provider-facing programs to increase ACP, [12][13][14][15][16][17] overall rates of ACP have not increased appreciably among diverse older adults in the US. 7 ACP is a complex, socially mediated behavior 18,19 ; thus, as with other socially mediated health behaviors, such as physical activity, blood pressure management, and tobacco use, [20][21][22] it is likely that community-level factors influence ACP.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Known barriers to ACP include individual (eg, knowledge, attitudes) and health system level (eg, complexity of advance directive forms, lack of clinician training) factors. However, despite development of patient-and provider-facing programs to increase ACP, [12][13][14][15][16][17] overall rates of ACP have not increased appreciably among diverse older adults in the US. 7 ACP is a complex, socially mediated behavior 18,19 ; thus, as with other socially mediated health behaviors, such as physical activity, blood pressure management, and tobacco use, [20][21][22] it is likely that community-level factors influence ACP.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers are tasked with educating patients about ACP. Studies have shown their ability, skills, knowledge, and attitudes influence AD communication and patient education across disciplines 3 in medicine, 4 nursing, 5 and social work. However, multiple barriers, including lack of consideration of patients' values and beliefs, contribute to poor delivery of healthcare information.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found Latino culture as important to consider toward avoiding discussions about death and documenting a living will. 19 Additionally, consistent with a cross-sectional study examining Latino preferences for planning and EOL care, participants had not communicated their preferences to family members or their providers. 31 Although Latinos appear to prefer family-centered decision-making for EOL care, they may not want to burden others about distressing issues such as the possibility of dying and preparing for death.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing counseling used for the intervention involved older Latinos in ACP, targeting their readiness to engage in ACP communication with others (eg, doctors, nurses, and/or family members) and desire to plan for EOL care by documenting an AD. 19 TX group participants receiving MI counseling were guided toward the complex topic of death and dying, allowing them to ask questions about ACP and documenting an AD involving (1) the living will and (2) durable power of attorney for health-care decision-making. Motivational interviewing counseling was delivered by a social worker with an advanced level of education in social work at the master's level.…”
Section: Methodsmentioning
confidence: 99%